Sosialisasi Pemanfaatan Program Corporate Social Responsibility (CSR) bagi Pelaku Usaha - Elly Yuliawati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2020)
Sawarna Beach Tourism offers an atmosphere of beautiful nature that is different from other tourist attractions in Indonesia. Given the distance of this location from the center of the City of Banten residents and the local tourism agency initiated a homestay that can be used to spend the night for local and foreign tourists. The homestay is able to provide a place to unwind, have a good sleep, eat well, take a bath and change clothes adequately. Therefore facilities and infrastructures homestay must continue to be developed and upgraded accordance with the times. The purpose of this community service is to direct business owners' homestay in targeting programs Corporate Social Responsibility (CSR) from companies in the Banten province environment to develop their businesses. By providing CSR programs, companies can ethically contribute to the development of their social and business environments. This can be a solution to business continuity and sustainable strategic partnerships. The results of the training show the addition of knowledge and understanding, participants can find out about CSR and take advantage of opportunities from the company's CSR program in developing their businesses, know the stages and strategies in an effort to obtain funding for CSR programs, and most importantly there is a desire to try to take advantage of the Company's CSR programs in the environment around their region.